2017
DOI: 10.1371/journal.pone.0181424
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of operative time in thyroid surgery: A prospective multicenter study of 3454 thyroidectomies

Abstract: ObjectiveTo identify the determinants of operative time for thyroidectomy and quantify the relative influence of preoperative and intra-operative factors.BackgroundAnticipation of operative time is key to avoid both waste of hospital resources and dissatisfaction of the surgical staff. Having an accurate and anticipated planning would allow a rationalized operating room use and may improve patient flow and staffing level.MethodsWe conducted a prospective, cross-sectional study between April 2008 and December 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 30 publications
3
16
2
Order By: Relevance
“…Operative time is greatly influenced by the surgeon's experience, as shown by Patoir et al (11). The mean operating time in this study was not statistically significantly different between groups, or from the average time of 86 minutes reported in the literature.…”
Section: Discussionsupporting
confidence: 39%
“…Operative time is greatly influenced by the surgeon's experience, as shown by Patoir et al (11). The mean operating time in this study was not statistically significantly different between groups, or from the average time of 86 minutes reported in the literature.…”
Section: Discussionsupporting
confidence: 39%
“…The association between prolonged operative time and anasotmotic leak following esophagectomy, while also a novel finding, is more straightforward . Intuitively, longer operative times may frequently represent more technically challenging cases, which could inherently be expected to have an increased risk of anastomotic complications.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, others have also reported that anatomic factors significantly influence operative time and reflect operative complexity for rectal and hepatic resections. However, Patoir et al found that surgeon characteristics and center location accounted for 32% and 29%, respectively, of operative time variation during thyroid surgery, suggesting that factors other than operative complexity may also contribute to operative time. In consideration of the above, the etiology of prolonged operative time is likely multifactorial and varies across surgical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Although Consorti OT. [40][41][42] On univariate analysis, we found preoperative history of Graves' to be significantly associated with increased OT; however, this relationship was not significant on multivariate analysis. Preoperative thyroiditis was not significant on either univariate or multivariate analysis.…”
Section: Discussionmentioning
confidence: 60%